KARAKTERISTIK BATAKO RINGAN YANG MENGGUNAKAN AGREGAT PARTIKEL PELEPAH NIPAH (Nypa fruticans Wurmb.) - Muchlas Dharmawan Tualle (Program Studi Kehutanan Universitas Muslim Maros, 2021)
This research aimed to determine the effect of aggregate nypa trunk particles composition and the addition of CaCl2 accelerator in physical and mechanical characteristics of lightweight concrete-block. The testing procedure was performed based on ASTM C 90-09 standard for oven-dry density test, water absorption, and compressive strength. The results showed that the difference of nypa trunk particle composition in lightweight concrete-blocks mixture influenced the oven-dry density, water absorption, and compressive strength values of lightweight concerete-block, otherwise the addition of CaCl2 accelerator in lightweight concrete-block mixture has no effect on oven-dry density value, water absorption and compressive strength. The larger of the nypa trunk particles composition in the lightweight concrete-block mixture obtain lower oven-dry density, higher water absorption, and lower compressive strength. The lightweight concerete-block from aggregate of nypa trunk particles in this research did not qualify ASTM C 90-09, because water absorption and compressive strength values were not eligible.